2016
DOI: 10.1016/j.rser.2015.12.268
|View full text |Cite
|
Sign up to set email alerts
|

Advances in nanostructured thin film materials for solar cell applications

Abstract: This paper reviews recent advances in photovoltaic devices based on nanostructured materials and film designs, focusing on cadmium telluride (CdTe), copper zinc tin sulphide (CZTS), dye-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(61 citation statements)
references
References 137 publications
1
58
0
2
Order By: Relevance
“…Метод 3 заключался в расчете глубины половинного слоя ослабления рентгеновских лучей по формуле, представленной в [2]:…”
Section: объекты и методика экспериментаunclassified
See 1 more Smart Citation
“…Метод 3 заключался в расчете глубины половинного слоя ослабления рентгеновских лучей по формуле, представленной в [2]:…”
Section: объекты и методика экспериментаunclassified
“…Халькогениды цинка и особенно кадмия нашли широ-комасштабное наземное применение в тонкопленочных солнечных элементах (СЭ) [2,3] благодаря максималь-ному среди полупроводниковых материалов теоретиче-скому коэффициенту полезного действия (свыше 29% для CdTe и 17% для CdSe). Считается, что это обу-словлено большими значениями ширины запрещенной зоны (свыше 1 eV), оптимальными для фотоэлектриче-ского преобразования солнечного излучения в наземных условиях.…”
Section: Introductionunclassified
“…Their preliminary work on this graded bandgap devices showed over 10% efficiency with extremely high J sc~4 8 mA/cm 2 . In the case of organic-inorganic NCs hybrid solar cells, metal oxides have the ability to attain high efficiency as they have several scales of pores which may shorten the carrier diffusing length [83]. Using different passivation layers (ZnSe or CdS) and changing different metal oxide thicknesses are also possible ways of improving the efficiency of CdTe NC-based solar cells [84,85].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…It leads to increase in the effective diffusion length of minority carrier, which ultimately leads to poor solar cell performance [19]. Ali et al [20] have reported that voids can adversely affect the electrical and optical properties of the films. Hence, both agglomeration and voids are not desired.…”
Section: Introductionmentioning
confidence: 99%